3D printing and high tibial osteotomy. Issue 5 (21st May 2018) - Jones, Gareth G.; Jaere, Martin; Clarke, Susannah; Cobb, Justin
Abstract : High tibial osteotomy (HTO) is a relatively conservative surgical option in the management of medial knee pain. Thus far, the outcomes have been variable, and apparently worse than the arthroplasty alternatives when judged using conventional metrics, owing in large part to uncertainty around the extent of the correction planned and achieved. This review paper introduces the concept of detailed 3D planning of the procedure, and describes the 3D printing technology that enables the plan to be performed. The different ways that the osteotomy can be undertaken, and the varying guide designs that enable accurate registration are discussed and described. The system accuracy is reported. In keeping with other assistive technologies, 3D printing enables the surgeon to achieve a preoperative plan with a degree of accuracy that is not possible using conventional instruments. With the advent of low dose CT, it has been possible to confirm that the procedure has been undertaken accurately too. HTO is the 'ultimate' personal intervention: the amount of correction needed for optimal offloading is not yet completely understood. For the athletic person with early medial joint line overload who still runs and enjoys life, HTO using 3D printing is an attractive option. The clinical effectiveness remains unproven. Cite this article: EFORT Open Rev 2018;3 DOI: 10.1302/2058-5241.3.170075.